The Study of Spurt of Blood in the lens of The Theatre of Cruelty - Fatemeh Sadat Basirizadeh; Narges Raoufzadeh; Shiva Zaheri Birgani (Britain International for Academic Research (BIAR-Publisher), 2022)
This paper explains Antonin Artaud's Spurt of Blood in the lens of The Theatre of Cruelty. Antonin Artaud is one of the most famous writers in the history of theatre. Antonin Artaud is considered to be the main contributor to the ideologies of Theatre of Cruelty in the early twentieth century as a reaction to the generic and ordinary ways in which theatre was created In Antonin Artaud's A Spurt of Blood examines subjects that may appear frightening to the general public such as blasphemy against God and the idea of innocence being reversed to lust, or love to depravity, or security to terror.